Pengaruh Penggunaan Ekstrak Kasar (Daun Cengkeh, Batang Serai dan Daun Kemangi) sebagai Salah Satu Teknik Imoltilisasi Benih Ikan Mas (Cyprinus carpio) pada Transportasi Basah - mutmainnah, mutmainnah; Yanto, Subari; Mustarin, Amirah (Agricultural Technology Education Study Program, 2024)
This study aims to analyze the effect of using crude extracts (clove leaves, lemongrass stems and basil leaves) in the immoltilization process of carp seeds in wet transportation. The research method used was a completely randomized design (CRD) with 4 tretments and 3 replication for each treatment. The variables observed in this study were fish induction time, fish sedative time, survival and water quality parameters (temperature, DO and pH). Data were processed using the SPSS program with Analysis (ANOVA) and Kruskal-Wallis. The results showed that the administration of crude extracts (clove leaves, lemongrass stems and basil leaves) had a significant effect on the process of immoltilization of carp seeds on wet transportation with the best treatment of basil crude extracts with 87% survival rate optimal induction time of less than 3 minutes (152 seconds) and optimal sedative time of less than 5 minutes (272 seconds).